Serum biochemical reference ranges for pregnant sheep - Laura Ferrari Monteiro Varanis; Karla Alves Oliveira; Carolina Moreira Araújo; Wendell Fernando Guimarães da Cruz; Gilberto de Lima Macedo Júnior (Bioscience Journal, 2021)
Late pregnancy is accompanied by dramatic changes in the metabolism of sheep, in which the nutrient requirements increase and the metabolic capacity of ewes is under severe stress due to the rapid foetal growth and development of the mammary gland. The blood metabolic profile can be used to monitor these alterations, which can lead to metabolic disorders such as pregnancy toxaemia. However, data available on serum parameters in sheep do not consider physiological state. Therefore, the present study aimed to determine the biochemical reference ranges for pregnant ewes, including serum energy, protein and enzyme-related metabolites. Data from a variety of metabolites were obtained from experiments performed in several institutions and commercial farms using Santa Inês, Dorper, Lacaune, Morada Nova, Bergamacia and Suffolk ewes reared under different conditions (grazing, feedlot, semi-feedlot, collective and/or individual pens, and metabolic cages) from 2006 to 2017. All animals were healthy and without feed restriction. Data from ewes with any clinical manifestations were removed. The metabolic energy profile included data of glucose, cholesterol, triglyceride, high-density lipoprotein, low-density lipoprotein and very-low-density lipoprotein levels; the metabolic protein profile included the metabolites total protein, uric acid, urea, albumin, and creatinine; and the metabolic enzymatic profile included the enzymes aspartate aminotransferase, gamma-glutamyl transferase and alkaline phosphatase. The reference ranges were estimated using the software RefVal 4.11. Dixon’s test was used to identify and remove outliers. The confidence intervals and percentiles were estimated using the nonparametric method of bootstrap when data were not normally distributed. A 95% confidence level was used. The serum biochemical reference ranges for pregnant sheep determined in our study were strongly divergent from those established by one of the most cited books on the topic, especially considering the high serum urea and cholesterol concentrations and low levels of blood glucose observed. Therefore, it is essential to consider physiological status when evaluating the blood metabolic profile of pregnant ewes in order to maintain an adequate nutritional management and to prevent health disorders that may lead to productive and reproductive losses.